2018
DOI: 10.18535/ijsrm/v6i8.m01
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Connection Profile of Junior High School Students in Solving Mathematical Problems based on Gender Difference

Abstract: This study aimed at describing the mathematical connection profile of Junior High School students in solving mathematical problems based on gender difference. The subjects were two eighth grade students who had the same math ability. They were one male student and one female student. Subjects were selected by giving a math ability test, and based on the same scores at a middle level. The research type was exploration with a qualitative approach. Data were taken by interviewing the subject in depth on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
(4 reference statements)
2
7
0
1
Order By: Relevance
“…Also, they concluded that the understanding of the derived concept will be promoted when meanings of rate of change, limit, and function are constructed and connected in different contexts. Furthermore, we agreed with Pambudi et al (2018) given that, we find that success in problem-solving depends on the mathematical connections that a subject makes. In the case of P1, the result of task 3 was not successful, due to a disconnection or a mathematically inconsistent procedure.…”
Section: Figure 17 Evidence Of Disconnection In the Procedures Done By P1supporting
confidence: 77%
See 1 more Smart Citation
“…Also, they concluded that the understanding of the derived concept will be promoted when meanings of rate of change, limit, and function are constructed and connected in different contexts. Furthermore, we agreed with Pambudi et al (2018) given that, we find that success in problem-solving depends on the mathematical connections that a subject makes. In the case of P1, the result of task 3 was not successful, due to a disconnection or a mathematically inconsistent procedure.…”
Section: Figure 17 Evidence Of Disconnection In the Procedures Done By P1supporting
confidence: 77%
“…Since, when a student makes mathematical connections between concepts, representations, meanings and between mathematics and real life, he could better understand a mathematical concept (Evitts, 2004;National Council of Teachers of Mathematics [NCTM], 2000;Özgen, 2013). Furthermore, Pambudi, Budayasa and Lukito (2018) affirmed that "mathematical connections have a close relationship with "problem-solving", in which the ability of students to connect mathematical ideas will determine the success of students in solving mathematical problems " (p. 74). This allows us to ensure that it is important to link the mathematical problem-solving with mathematical connections, in fact, the connections arise when students or teachers solve tasks and can be identified in the worksheets, in oral or mimic arguments (García-García & Dolores-Flores, 2018), and appear in the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa hasil penelitian menunjukkan kesamaan proses perkembangan berfikir matematika dan prestasi matematika antara siswa laki-laki dan perempuan (Ajai, & Imoko, 2015;Nugraha & Pujiastuti, 2019;Lestari, Suesthi, & Wiyono, 2019;Ghasemi, & Burley, 2019;Kersey, Csumitta, & Cantlon, 2019;Kamid, Rusdi, Fitaloka, Basuki, & Anwar, 2020). Di pihak lain, ada peneliti yang melaporkan bahwa ada perbedaan dalam proses berpikir dan prestasi matematika, di mana siswa laki-laki umumnya lebih unggul dari siswa perempuan (Tommaso, Mendolia, & Contini, 2016;Kwanza, Maikudi, Taiwo, © Vintseh, Usman, Attah, & Alaku, 2018;Pambudi, Budayasa, & Lukito, 2018), khususnya pada keahlian visual matematis (Aini, & Hasanah, 2019). Adapun, siswa perempuan lebih cermat dalam perhitungan dibandingkan dengan siswa laki-laki (Febriyanti & Masriyah, 2016).…”
Section: Pendahuluanunclassified
“…Connections are more important because they support students to increase understanding of the relationship between mathematical concepts and other science concepts (Pambudi, Budayasa, & Lukito, 2018). The mathematical connection skills make students and teachers try to find mathematics in real life, especially those related to students' lives and interests, relationships between mathematical concepts and knowing how mathematical concepts relate to other concepts and school lessons (Suharto & Widada, 2018).…”
mentioning
confidence: 99%
“…When the students learn a concept, then they need to learn the other ones. This state is called a mathematical connection, the ability of students in connecting a concept with the other concepts (Pambudi, Budayasa, & Lukito, 2018).…”
mentioning
confidence: 99%